Pengaruh Pupuk Hijau Kirinyuh (Chromolaena Odorata L.) dalam Mensubsitusi Pupuk Buatan pada Tanaman Semangka (Citrulus Lanatus) - Chairil Ezward; Elfi Indrawanis; Annisa Pebriani (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2023)
This research aims to determine the response of watermelon plants to the use of kirinyuh (Chromolaena odorata) green fertilizer. This research was carried out in Benai Kecil Village, Benai District, Kuantan Singingi Regency, Riau Province. The time for carrying out this research is from February to March 2023. The research method used was a non-factorial randomized block design (RAK), namely the dose of kirinyuh green fertilizer (K) consisting of 5 treatment levels. F0 = 100% Artificial fertilizer, F1= 25% Artificial fertilizer + 20 tons/ha Kirinyuh, F2 = 50% Artificial fertilizer + 20 tons/ha Kirinyuh, F3= 75% Artificial fertilizer + 20 tons/ha Kirinyuh and, F4 = No artificial fertilizer and no fertilizer. Each treatment was repeated 3 times so that there were 15 plots, the experiment in one plot consisted of 4 plants, 3 of which were sample plants. Based on the analysis of variance, the application of crunchy green fertilizer had a significant effect on all treatment parameters. The best treatment is found in F3 = 75% Artificial Fertilizer + 20 tons/ha Kirinyuh.